Structure and Modus Operandi of Code of Conduct Bureau and Public Complaints Commission in Enthroning Accountability in Governance: Nigeria Experience - Alao Olaleke Michael (RIRAI Publisher, 2020)
Laden with corruption, fear, and lack of job security, politicization reigns supreme; one would expect nothing short of low or poor performance of the accountability institutions in Nigeria. There have been lots of scholarly works on accountability, accountability institutions, administration and performance of one accountability institution or the other. It was revealed that majority of the studies examined the activities or performance of these accountability institutions. Most of the scholars that wrote on accountability institutions in Nigeria picked one institution at a time and more often than not, limit their study to limitations, challenges and impediments of performance; and/or at best bring out impediments of delivery of service. Some of the foreign scholars’ writings and works conformed to the peculiarities of their environment which is different from what exists in Nigeria of today. What they wrote did not foresee the influence of politics on administration and did not put peculiarity of Nigeria into consideration. Issues like above the law syndrome, sacred cows, godfatherism, nepotism, favouritism, etc were not considered. This study in its peculiar form, afforded the staff of Public Complaints Commission and Code of Conduct Bureau the opportunity for self-assessment and self auditing; they were bulk of the respondents for both the questionnaire administration and interview. Accountability institutions in Nigeria have been alleged of not performing up to expectation or not performing at all by the public. It is against this background that this study seeks to assess the structure and modus operandi of the Code of Conduct Bureau and Public Complaints Commission in enthroning accountability in Governance. The study found out from the available information collected through the administration of questionnaire and conduct of in-depth interview that the awareness of Public Complaints Commission (PCC) and Code of Conduct Bureau (CCB) is not in any way in-doubt amongst the elites in the country; the structure are perfect enough for the purpose for which it is set; there is cordial relationship between the superior and the subordinate; and there is room for free flow of information in the institutions.